The digital will - Aguas Valero, Gerardo (Revista de derecho aragonés, 2022)
If Jorge Gracia – a native of Calamocha – had died thirty years ago, the traditional institutions – contemplated in article 317 of the Código del Derecho Foral de Aragón – would have finally determined the destination of his assets peacefully. Three decades later we are witnessing a true metamorphosis in the matter and that is that the classic assets – with eminently patrimonial characteristics – currently coexist with others related to the personality of the deceased and this extreme – added to certain inaccuracies in the language used by the national legislator and that we will expose later – determines that we must analyze if our institutions are prepared to resolve the succession of citizens. This short article aims, therefore, to confirm the suitability and validity of the normative regime that regulates the destination of the assets of the deceased or, on the contrary, it is necessary to make some adjustment of greater or lesser depth in it.